Divergent reaction pathways in gold-catalyzed cycloisomerization of 1, 5-enynes containing a cyclopropane ring: dramatic ortho substituent and temperature effects. Issue 7 (29th March 2016) - Chen, Gen-Qiang; Fang, Wei; Wei, Yin; Tang, Xiang-Ying; Shi, Min
Abstract : Gold-catalyzed cycloisomerization of 1, 5-enynes containing a cyclopropane ring provides access to cyclobutane-fused 1, 4-cyclohexadiene, 1, 3-cyclohexadiene, tricyclic cyclobutene and biscyclopropane derivatives. Abstract : A gold(i )-catalyzed cycloisomerization of easily available 1, 5-enynes containing a cyclopropane ring has been developed, efficiently providing cyclobutane-fused 1, 4-cyclohexadiene, tricyclic cyclobutene, biscyclopropane and 1, 3-cyclohexadiene derivatives in moderate to excellent yields. When the phenyl group was not ortho substituted, 1, 4-cyclohexadienes could be produced. With an ortho substituent, three different products could be selectively synthesized by control of the temperature and the used gold(i ) catalyst. The 1, 5-enyne substrate first undergoes a classical enyne cycloisomerization to form a tricyclic cyclobutene key intermediate, which undergoes subsequent transformation to produce the desired products. A plausible reaction mechanism was proposed according to deuterium labeling experiments and intermediate trapping experiments, as well as DFT calculations. In our current reaction, the ortho substituent on the phenyl group controls the reaction outcome and the ortho substituent effect was found to originate from steric and electronic factors.